2019
DOI: 10.3389/fimmu.2019.00601
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro Assays to Assess the Modulation of Dendritic Cells Functions by Therapeutic Antibodies and Aggregates

Abstract: Therapeutic antibodies have the potential to induce immunogenicity leading to the development of anti-drug antibodies (ADA) that consequently may result in reduced serum drug concentrations, a loss of efficacy or potential hypersensitivity reactions. Among other factors, aggregated antibodies have been suggested to promote immunogenicity, thus enhancing ADA production. Dendritic cells (DC) are the most efficient antigen-presenting cell population and are crucial for the initiation of T cell responses and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…9,10 Some in vitro studies using human peripheral blood mononuclear cells (hPBMCs) have suggested that mAb aggregates induce inflammatory responses and innate immune responses, which may increase the risk for immunogenicity. [17][18][19][20] It has been reported that highly aggregated mAbs, but not the monomeric form, can enhance in vitro immune responses, and this activation has been shown to be inhibited by blocking toll-like receptor (TLR) 2, TLR4, Fc gamma receptors (FcgRs), and the complement system. 18 A recent study has suggested that aggregates of intravenous immunoglobulin and bevacizumab, but not human serum albumin, activated innate immune cells, primarily via FcgRs.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Some in vitro studies using human peripheral blood mononuclear cells (hPBMCs) have suggested that mAb aggregates induce inflammatory responses and innate immune responses, which may increase the risk for immunogenicity. [17][18][19][20] It has been reported that highly aggregated mAbs, but not the monomeric form, can enhance in vitro immune responses, and this activation has been shown to be inhibited by blocking toll-like receptor (TLR) 2, TLR4, Fc gamma receptors (FcgRs), and the complement system. 18 A recent study has suggested that aggregates of intravenous immunoglobulin and bevacizumab, but not human serum albumin, activated innate immune cells, primarily via FcgRs.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these human CSP mAbs are now being considered as tools for malaria control by passive transfer. Although mAbs may confer short-term protection, cost-benefit analyses may reveal hurdles in the mass administration of mAbs to infants and pregnant women (32,33). Structural data emerging from mAbs has, however, revealed vulnerabilities on parasite antigens that can now be utilized to design the next-generation malaria vaccines that focus the host response to a narrow range of protective epitopes, recapitulating the protective responses achieved by passive transfer of mAbs (34,35).…”
mentioning
confidence: 99%
“…Furthermore, we recently showed that ERK phosphorylation, but not p38 or JNK, was induced in moDC in response to infliximab aggregates. 12 Previous reports also demonstrated activation of MAPKs and NF-kB subunit p65 in moDC in response to danger signals such as lipopolysaccharide and contact sensitizers, such as nickel. 14,16,19 We were then interested in the upstream signaling pathways that participated in DC response to hGH aggregates.…”
Section: Discussionmentioning
confidence: 95%
“…The choice to focus on CXCL10 was made for 2 main reasons: first, it is an important chemokine playing a central role in T-helper cell polarization, and second, we described its production in response to hGH aggregates but not with therapeutic antibody aggregates. 12 To study intracellular mechanisms regulated in aggregatesstimulated moDC, we first showed that aggregates increased phosphorylation of p38 MAPK, ERK, JNK, as well as NF-kB subunit p65 binding. This observation seems in agreement with a recent study by Polumuri et al 18 also showing the implication of intravenous immunoglobulin and bevacizumab aggregates (shaken or stirred) in the activation of MAPKs in human peripheral blood mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%